ANALISIS TINGKAT KEPUASAN PENUMPANG TERHADAP KUALITAS LAYANAN BAJAJ MAXRIDE DI KOTA MAKASSAR - Marsanda, Suci Andriani (xxxx-xxxx, 2025)
Makassar is a metropolitan city with various types of public transportation, one of which is the Bajaj Maxride. This vehicle is a new vehicle so it is important to know the quality of service through the level of passenger satisfaction. The level of passenger satisfaction can be determined through a questionnaire and then analyzed using the Community Satisfaction Index (IKM) analysis. In this analysis there are 9 service elements which will then be assessed by Bajaj Maxride passengers. There are various levels of passenger satisfaction obtained, ranging from very satisfied, satisfied, dissatisfied, and less satisfied. From this level of satisfaction, the Bajaj Maxride service provider can then make decisions to improve service quality on service elements that are considered to have poor service quality, such as service quality on the elements of service requirements and service time